Reduced quality of life in patients with non-erosive gastroesophageal reflux disease - Vargas, Márcia; Dall’Alba, Valesca; Barros, Sergio Gabriel Silva de; Fagundes, Renato Borges (Clinical and Biomedical Research, 2017)
Introduction: Gastroesophageal reflux disease (GERD) is a highly prevalent condition in the Western world. It is a frequent cause of medical appointments and has a high impact on quality of life (QOL). This study aimed to assess health-related quality of life (HQ-QOL) of patients with non-erosive gastroesophageal disease (NERD) and compare their scores with the scores of patients with GERD symptoms and non-pathological acid reflux (non-NERD). Methods: We studied 42 patients with GERD symptoms—21 with positive pHmetry for acid reflux (NERD group) and 21 with negative pHmetry for acid reflux (non-NERD group). We enrolled patients matched by age and gender. Patient inclusion criteria were based on clinical and endoscopic findings and pHmetry. All other major diseases having an impact on QOL were excluded as well as patients in regular use of proton pump inhibitors, prokinetics, histamine-2 receptor antagonists and anti-depressants. All subjects were asked to fill in a validated translation of the SF-36 questionnaire. We described scores trough median and interquartile range (IQR) and assessed the significance of the comparisons through Mann-Whitney test and chi-square test or Student’s t-test when appropriate. Results: We found no significant differences in the eight domains of SF-36 between the two groups. Conclusion: QOL of patients with GERD symptoms was equivalent, regardless of acid reflux at pHmetry. Keywords: SF-36; quality of life; gastroesophageal reflux; pHmetry